DESAIN SISTEM KONTROL PENGGERAK MULA GENERATOR MAGNET PERMANEN PLTMH MENGGUNAKAN PLANETERY GEAR - Rizki Pratama Putra; Samsurizal Samsurizal; Novi Gusti Pahiyanti (KILAT, 2018)
Voltage and frequency stability of a micro hydro power plant requires a simple, reliable and efficient control system. This study aims to design a control system using planetary gear which is known to provide fast speed adjustments to respond to the changing rate of water flow. In this study the system design will be created using matlab simulink. The system will then be simulated with various turbine rotation conditions to see the reliability and stability of the frequency and voltage produced by the permanent magnet generator used in micro hydro power plant. The results obtained are the control system seems can stabilize the generator rotor rotation so that the resulting voltage frequency remains constant even though the input load and water flow rate are dynamic. From the simulation results it is also found that the efficiency of the control system is directly proportional to the difference in mechanical input and electric power output of the system.